2018
DOI: 10.1016/j.yebeh.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of stereoelectroencephalography (SEEG) in reevaluation of epilepsy surgery failures

Abstract: Management of patients after initial epilepsy surgical failure is challenging. In this study, we report our experience in using the stereoelectroencephalography (SEEG) method in the reevaluation of patients after initial epilepsy surgical failure. We selected 28 patients examined through SEEG in our department for drug-resistant focal epilepsy following initial epilepsy surgical failure. For each patient, the residual seizure onset zone (rSOZ) as defined by SEEG was classified as either contiguous if the seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Although surprising, it is becoming a well‐documented effect that culminates from a few reasons. First, with more sophisticated invasive EEG techniques and their reduced morbidity, there is a lower threshold for the use of invasive EEG to evaluate the epileptogenic network for surgical failures . Nonetheless, there are an increasing number of invasive evaluations that do not lead to subsequent resections in recent years .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although surprising, it is becoming a well‐documented effect that culminates from a few reasons. First, with more sophisticated invasive EEG techniques and their reduced morbidity, there is a lower threshold for the use of invasive EEG to evaluate the epileptogenic network for surgical failures . Nonetheless, there are an increasing number of invasive evaluations that do not lead to subsequent resections in recent years .…”
Section: Discussionmentioning
confidence: 99%
“…First, with more sophisticated invasive EEG techniques and their reduced morbidity, there is a lower threshold for the use of invasive EEG to evaluate the epileptogenic network for surgical failures. 23 Nonetheless, there are an increasing number of invasive evaluations that do not lead to subsequent resections in recent years. 24 Second, there has been a shift in the demographic of the presenting patient population from "straightforward" mesial temporal lobe epilepsies to more complex extratemporal and nonlesional substrates.…”
Section: Predictors Of Seizure Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…This is lower compared to a previous study reporting the SOZ being close to the previous resection margin at 35% with reoperation rate of 45% with Engel class I outcomes of 50%. 25 Reoperation was performed in nine patients (88%) in our study; but Engel class I outcome was 25%. Two of these patients with previous epilepsy surgery had previous IVEM.…”
Section: Surgical Outcomesmentioning
confidence: 66%
“…The epileptogenicity index (EI) (Bartolomei et al, 2008) has been shown to quantify the epileptogenicity of brain structures and has been validated with clinically identified probable EZ, seizure outcome following surgical resection, and with interictal high-frequency oscillation maps to identify EZ (Roehri et al, 2018;Vaugier et al, 2018). The EI statistically summarizes the spectral and temporal parameters of SEEG signals and relates to the propensity of a brain area to generate low voltage fast discharges.…”
Section: Quantification Of the Ezmentioning
confidence: 99%